The main directions of state support and regulation of small business in Azerbaijan (Economics and region, 2022)
Strengthening the role of small and medium-sized enterprises (SMEs) in the economy of Azerbaijan, increasing its competitiveness, expanding access to financial resources, improving mechanisms for its support, creating favorable conditions for the development of entrepreneurship in the regions, attracting local and foreign investment in this area, diversifying the country's economy and ensuring its sustainability are strategic goals of the state policy. Small business entities occupy a significant place among market participants. In terms of their organizational structures, management systems, marketing strategies, and rules of legal organization, small businesses differ sharply from other participants. This difference is manifested in their market share, action plans, as well as in the fact that they bring more benefits to society and higher returns for the state and gross domestic product. The article analyzes the ways and methods of state support of small business enterprises in Azerbaijan. It is noted that the country has established the Council of Entrepreneurs, which plays the role of an instrument for active participation of the private sector in public investment projects related to infrastructure, as well as the introduction of various forms of cooperation between the state and business. Indeed, in recent years, significant amounts of funds have been allocated from the state budget for investment projects, while preferential loans are provided to finance various investment projects through the National Fund for Entrepreneurship Support. It is important to note the growing role of entrepreneurship in the restoration and economic development of the territories liberated from occupation. Therefore, the participation of local investors in the development of the region is important. Entrepreneurs and businessmen should create business here, use the opportunities created for them by the state and contribute to the development of the region. Entrepreneurs have the opportunity to create and conduct business in the territories liberated from occupation in the areas of construction, tourism, production, supply of agricultural products and their processing, as well as trade and various types of services. In addition, there is no competition in these areas yet, so the first investments will bring more profit. As for the expectation of additional benefits for doing business and entrepreneurial activity in the liberated regions, according to the decree of December 10, 2021 on accelerating economic development in the territories freed from occupation, great benefits are provided for entrepreneurs.
Keywords: Azerbaijan; small business; regulation; state-business cooperation; businessmen’s education; competition; benefits for entrepreneurs